2011
DOI: 10.1088/0957-0233/22/10/104019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between wire mesh sensor and gamma densitometry void measurements in two-phase flows

Abstract: Wire mesh sensors (WMS) are fast imaging instruments that are used for gas–liquid and liquid–liquid two-phase flow measurements and experimental investigations. Experimental tests were conducted at Helmholtz-Zentrum Dresden-Rossendorf to test both the capacitance and conductance WMS against a gamma densitometer (GD). A small gas–liquid test facility was utilized. This consisted of a vertical round pipe approximately 1 m in length, and 50 mm internal diameter. A 16 × 16 WMS was used with high spatial and tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 25 publications
0
18
0
2
Order By: Relevance
“…When inlet air flow rate remains constant, differential pressure decreases with the decrease of inlet water flow rate. Differential pressure subtracted from two absolute pressure sensors was fed into mathematical model in equation (11). The change of air void fraction with air/water flow rate is illustrated in Figure 4.…”
Section: Differential Pressure Correlation For Void Fractionmentioning
confidence: 99%
See 1 more Smart Citation
“…When inlet air flow rate remains constant, differential pressure decreases with the decrease of inlet water flow rate. Differential pressure subtracted from two absolute pressure sensors was fed into mathematical model in equation (11). The change of air void fraction with air/water flow rate is illustrated in Figure 4.…”
Section: Differential Pressure Correlation For Void Fractionmentioning
confidence: 99%
“…Both ERT and WMS can measure gas void fraction without the consideration of friction loss in the two-phase flow, which provides an alternative approach to validate the gas void fraction model based on differential pressure. The void fraction measurement accuracy of ERT and WMS were discussed by Faraj [10] and Sharaf [11]. The principle behind ERT is to determine the electrical conductivity by measuring the voltage between the ERT electrodes mounted on the internal circumference of the conveying conduit.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial resolution is 3 mm which also equals the pitch of the wires. The technique has been tested by carrying out simultaneous measurements with other techniques, i.e., using Electrical Capacitance Tomography , gamma-ray absorption (Sharaf et al, 2011), ultrafast X-ray tomography Zhang et al (2013) and found to produce good agreement between the instruments.…”
Section: Wire Mesh Sensormentioning
confidence: 99%
“…However, the data from the first WMS is used to calculate time-averaged flow quantities such as liquid holdup, liquid film height, wetted wall perimeter and interfacial surface area. The effect of the WMS intrusiveness on these quantities is considered minimal based on the comparisons of WMS data with other non-intrusive tomographic techniques reported in the literature [29][30][31][32][33][34][35]. The sensors are installed in the second run of the flow loop (Fig.…”
Section: List Of Symbolsmentioning
confidence: 99%